THE EFFECT OF PICTURE AS MEDIA TO THE STUDENTS’ ACHIEVEMENT IN VOCABULARY - Siti Julaiha; Diani Syahputri; Syafrina Prihatini (English Education Study Program FKIP Universitas Alwashliyah Medan, 2022)
The objective of this research is to find out the significant effect of applying pictures on the students’ achievement in mastering vocabularies. The research was conducted at MTs. Hidayatullah Tanjung Morawa Medan. The research method used was experimental research design. The total population was 60 students in the seventh grade. There were two parallel classes that were selected as samples by using the cluster random sampling technique. One class was selected as an experimental group taught using pictures as media to master vocabulary and the other was selected as a control group taught using the lecturing method. Each group consisted of 30 students for each. The total sample was 60 students. The research instrument used was multiple-choice tests. Obtaining the mean score, standard deviation, and standard error of both groups, the statistic t-test was then carried out. It was obtained that to=1.681 and ttable=1.67 with df=58 at tcritical 0.05. This value determined that to was higher than ttable or 1.68>1.67, thus, the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected. In a conclusion, there was a significant effect of using pictures as media on students’ achievement in vocabulary mastery.